Light gauze for toughening fiber composite material and preparation method thereof

By using the lightweight mesh with alternating distribution of low melting point and high melting point components prepared by electrospinning in the VARI process, the problem of insufficient toughness between composite materials is solved, and a significant improvement in mechanical properties is achieved.

CN119433832APending Publication Date: 2025-02-14JIANGSU NEW HORIZON ADVANCED FUNCTIONAL FIBER INNOVATION CENT CO LTD

Patent Information

Application Number
CN202411771632.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The interlayer toughness of composite materials prepared by the VARI process is relatively poor, which limits its application in composite structures with the main bearing capacity.

Method used

A lightweight mesh yarn consisting of a low melting point component (A wire) and a high melting point component (B wire) is used to alternately and evenly distribute through electrospinning technology to form an isotropic mesh. The low-melting point component is insoluble in epoxy resin, and the high-melting point component is soluble in epoxy resin, which plays the role of bonding and toughening respectively.

Benefits of technology

The interlayer fracture toughness and post-impact compression strength of dry fiber composite materials are significantly improved, and the overall mechanical properties of composite materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433832A_ABST
    Figure CN119433832A_ABST
Patent Text Reader

Abstract

The invention relates to a lightweight gauze for toughening a fiber composite material and a preparation method thereof, belongs to the technical field of toughened gauzes, and solves at least one of the problems that in the prior art, the gauze is easy to dissolve in a resin filling process, the liquid forming effect is poor, the toughening effect is not obvious and the like. The light gauze comprises a low-melting-point component and a high-melting-point component; the melting point range of the low-melting-point component is 100-160 DEG C, and the low-melting-point component and the epoxy resin are insoluble; the melting point range of the high-melting-point component is 300 DEG C or above, and the high-melting-point component is dissolved in the epoxy resin. The light gauze is not easy to dissolve in the resin filling process, so that the manufacturability of automatic laying and liquid forming in the fiber composite material preparation process is improved; the brittleness of the dry fiber composite material is improved, and the mechanical property of the dry fiber composite material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of toughened mesh yarns, and in particular to a lightweight mesh yarn used for toughening fiber composite materials and a preparation method thereof. Background Art

[0002] The VARI process, also known as the Vacuum Assisted Resin Infusion process, is a molding technology for making large-scale composite parts. The core of this technology is to remove the gas in the fiber reinforcement through a vacuum state without using an autoclave, and use the flow and penetration of the resin to achieve the impregnation of the fiber and its fabric. Subsequently, it is cured under certain temperature conditions to form a final product with a certain resin / fiber ratio. However, the interlayer toughness of the composite material prepared by the VARI process is relatively poor, which limits its application in the main load-bearing composite material structure. The use of high-performance toughening materials to prepare lightweight non-woven materials to form interlayer toughening can effectively improve this problem.

[0003] Dry fiber (dry tape) or dry fiber preform, as the core material of VARI process, is composed of carbon fiber tape, setting agent and lightweight mesh. Compared with prepreg tape, it has low resin content and does not need low temperature for storage and transportation. With automatic tape laying technology and liquid molding process, it has obvious production efficiency and cost advantages. The mesh layer is a lightweight non-woven material used for interlayer toughening.

[0004] At present, the mesh used for interlayer toughening can be divided into amorphous thermoplastic resins (such as PES, PEI, etc.) and crystalline thermoplastic resins (such as PA, PET, etc.). Amorphous thermoplastic resins are soluble in epoxy resins because they have hydroxyl endcapping and a repeating unit structure similar to that of epoxy resins (similar dissolves in water). This also leads to partial dissolution of the mesh during the epoxy resin infusion process, resulting in uneven distribution of the mesh, thereby affecting the processability of liquid molding (slow penetration in the thickness direction or uneven penetration speed). Although crystalline thermoplastic resins are insoluble in epoxy resins, their toughening effect is poorer than that of amorphous thermoplastic resins, resulting in no obvious improvement in the mechanical properties of the prepared composite materials. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide an aramid spinning post-processing system and a post-processing method to solve at least one of the problems of poor temperature detection accuracy and poor temperature control accuracy of existing aramid fibers.

[0006] In view of the above analysis, an embodiment of the present invention is intended to provide a lightweight mesh yarn for toughening fiber composite materials, comprising:

[0007] The components of the light mesh yarn are a low melting point component and a high melting point component;

[0008] The melting point range of the low melting point component is 100-160° C., and the low melting point component is incompatible with the epoxy resin;

[0009] The high melting point component has a melting point range of above 300° C., and the high melting point component is miscible with the epoxy resin;

[0010] The light mesh yarn is woven by using A wire with a lower melting point and B wire with a higher melting point;

[0011] The A wires and the B wires both have nano-scale fiber structures, the A wires and the B wires in the light mesh are alternately and evenly distributed, and the light mesh is isotropic;

[0012] The surface density of the lightweight mesh is 4 to 20 g / m 2 , thickness is 15~80μm.

[0013] Preferably, the A wire is subjected to a hot pressing process during the laying process to play a role in bonding the carbon fiber tape, thereby ensuring the structural integrity of the dry fiber preform; and the B wire still maintains a complete structure after the hot pressing process, thereby ensuring the interlayer distance of the composite material.

[0014] Preferably, during the resin infusion process, the high melting point component can maintain the skeleton structure and promote resin conduction. During the curing process, due to similar miscibility, it plays a role of ex-situ toughening.

[0015] Preferably, the low melting point component is a crystalline thermoplastic resin, and the high melting point component is an amorphous thermoplastic resin.

[0016] Preferably, the low melting point component is one or more of polyamide, polyacrylonitrile, polyurethane, polyester, and / or the high melting point component is one or more of polyether sulfone, polyether imide, polyether ether ketone, polyether ketone.

[0017] A method for preparing a lightweight mesh, used for preparing the lightweight mesh, the method comprising:

[0018] S1: Weigh or measure the low melting point component of A silk and the solvent according to the preset formula and mix them, and stir them under heating until they are evenly mixed to obtain solution A;

[0019] S2: Weigh or measure the high melting point component of B silk and the solvent according to the preset formula and mix them, and stir them under heating until they are evenly mixed to obtain solution B;

[0020] S3: Injecting solution A and solution B into alternating needles of the array electrospinning device, that is, injecting solution A and solution B into any adjacent needles, respectively, and setting process parameters and winding speed;

[0021] S4: Perform electrospinning to obtain a finished lightweight mesh yarn.

[0022] A method for using a light mesh, characterized in that the light mesh is used, and the method comprises:

[0023] Laying:

[0024] The carbon fiber mother tape is unwound, the lightweight mesh yarn is laid on the upper layer of the carbon fiber tape and laminated, and then a setting agent is sprinkled, and a hot pressing process is set at the same time;

[0025] Liquid Forming:

[0026] The dry fiber preform is layered and infused with epoxy resin under vacuum pressure. After curing, a dry fiber composite material is obtained to realize the use of lightweight mesh.

[0027] A method for preparing a dry fiber composite material, using the above-mentioned lightweight mesh yarn, the preparation method comprising:

[0028] Laying:

[0029] The carbon fiber mother tape is unwound, the lightweight mesh yarn is laid on the upper layer of the carbon fiber tape and laminated, and then a setting agent is sprinkled, and a hot pressing process is set at the same time;

[0030] Liquid Forming:

[0031] The dry fiber preform is layered, epoxy resin is infused under vacuum pressure, and a dry fiber composite material is obtained after curing.

[0032] The preparation of the lightweight mesh comprises:

[0033] Weigh or measure the low melting point component of A silk and the first solvent according to the preset formula, mix them, and stir them under heating until they are evenly mixed to obtain solution A;

[0034] Weigh or measure the high melting point component of B silk and the second solvent according to the preset formula, mix them, and stir them under heating until they are evenly mixed to obtain solution B;

[0035] Solution A and solution B are injected into alternating needles of the array electrospinning equipment respectively, that is, the liquid injected into any adjacent needles is solution A and solution B respectively, and the process parameters and winding speed are set: liquid supply: 0.5-6 ml / h, +20-35 kV voltage is set at the needle, -5-0 kV voltage is set in the receiving area, spinning spacing is 10-30 cm, ambient temperature is 30-42 ° C, ambient relative humidity is 33-48%, and winding speed is 0.1-17 m / min to prepare A and B filaments alternately and evenly distributed, isotropic lightweight mesh yarn.

[0036] Preferably, the first solvent or the second solvent is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), anhydrous formic acid, acetic acid, and ethyl acetate.

[0037] A dry fiber composite material is prepared by the above-mentioned preparation method of the dry fiber composite material, and the preparation method of the dry fiber composite material comprises:

[0038] S1: Weigh or measure the low-melting-point component of A silk and the first solvent according to a preset formula, mix them, and stir them under heating conditions until they are evenly mixed to obtain solution A; wherein the composition of solution A is as follows by mass percentage: 5-30% of the low-melting-point component and 70-95% of the first solvent; wherein the melting point range of the low-melting-point component is 100-160° C., and the low-melting-point component is incompatible with the epoxy resin; and the low-melting-point component is polyacrylonitrile;

[0039] S2: according to a preset formula, weigh or measure the high melting point component of B silk and the second solvent, mix them, stir them under heating conditions until they are evenly mixed, and obtain solution B; the composition of solution B is as follows by mass percentage: 8-35% of high melting point component and 65-92% of second solvent; the melting point range of the high melting point component is above 300°C, and the high melting point component is miscible with epoxy resin; the high melting point component is one or more of polyethersulfone, polyetherimide, polyetheretherketone, and polyetherketone;

[0040] S3: Inject solution A and solution B into alternating needles of the array electrospinning device, that is, inject solution A and solution B into any adjacent needles, respectively, and set process parameters and winding speed; the process parameters in step S3 are: liquid supply: 0.5-6 ml / h, +20-35 kV voltage at the needle, -5-0 kV voltage at the receiving area, spinning spacing of 10-30 cm, ambient temperature of 30-42 ° C, ambient relative humidity of 33-48%, and winding speed of 0.1-17 m / min;

[0041] S4: performing electrospinning to obtain a finished lightweight mesh; the lightweight mesh is obtained by electrospinning, the needles for preparing A filaments and the needles for preparing B filaments are alternately and evenly distributed, and the lightweight mesh spun by the entire needle array consists of A filaments and B filaments, and A filaments and B filaments are respectively obtained by spinning solution A and solution B;

[0042] S5: Laying: unwinding the carbon fiber tape, laying the lightweight mesh yarn on the upper layer of the carbon fiber tape and laminating it, then sprinkling a setting agent, and setting a hot pressing process at a temperature of 100 to 160° C., and then obtaining a dry fiber preform through pre-slitting, winding and other processes;

[0043] S6: Liquid molding: The dry fiber preform is layered and infused with epoxy resin under vacuum pressure, and a dry fiber composite material is obtained after curing.

[0044] Preferably, the epoxy resin is a bisphenol A epoxy resin. In a specific implementation, the resin infusion time is compressed to 10 minutes or even shorter. During the resin infusion process, the high melting point component can maintain the skeleton structure and promote the resin flow. During the curing process, due to the similarity of the components, it plays a role of ex-situ toughening.

[0045] The A and B fibers both have nano-scale fiber structures; the surface density of the lightweight mesh yarn is 4 to 20 g / m 2 , thickness is 15 to 80 μm; A wire is a crystalline thermoplastic resin, and B wire is an amorphous thermoplastic resin;

[0046] The dry fiber composite material type I interlaminar fracture toughness can reach a maximum of 0.82KJ / m 2 , the maximum type II interlaminar fracture toughness can reach 2.43KJ / m 2 The maximum compression strength after impact can reach 244.5MPa.

[0047] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0048] 1. The dry fiber composite material prepared by the lightweight mesh provided by the present invention has good toughness and excellent mechanical properties. The present invention uses A wire with a lower melting point and B wire with a higher melting point to weave the lightweight mesh together, wherein the A wire can play a role in bonding the carbon fiber tape (melting) during the hot pressing process during the laying process, thereby ensuring the structural integrity of the dry fiber preform; the B wire still maintains a complete structure after the hot pressing process, thereby ensuring the interlayer distance of the composite material, ensuring that the fiber volume content is in a suitable range (50-60%), and further ensuring the mechanical properties of the composite material. In addition, although the low-melting-point component (A wire) melts during the laying process, it still has a certain toughening effect (particle / fiber bridging), which can synergistically enhance the toughness of the composite material with the high-melting-point component.

[0049] The dry fiber composite material type I interlaminar fracture toughness can reach 0.82KJ / m 2 , Type II interlaminar fracture toughness can reach 2.43KJ / m 2 , the compression strength after impact can reach 244.5MPa. Type I interlaminar fracture toughness G ⅠC and mode II interlaminar fracture toughness G ⅡC They are two test standards for composite materials, and both are test methods used to evaluate the mechanical properties of composite materials.

[0050] 2. The lightweight mesh provided by the present invention has good bonding effect with the carbon fiber tape and good laying processability; it is conducive to resin infusion and has good liquid molding processability. When the lightweight mesh provided by the present invention is used to prepare dry fiber composite materials, a hot pressing process is set in the laying link, and the hot pressing temperature matches the melting point of the low-melting-point component, so that the mesh and the carbon fiber have good carbon bonding effect and the laying processability is improved; the high-melting-point component (B wire) maintains a complete structure, so that it can act as a "skeleton" in the process of liquid molding to promote resin diversion, greatly improving the processability of liquid molding. In specific implementations, the resin infusion time can be compressed to 10 minutes or even shorter to complete the infusion.

[0051] 3. The preparation process of the lightweight mesh provided by the present invention is simple and the raw materials are easily available. The present invention adopts an array electrospinning method with alternating needles to realize a one-step preparation of lightweight mesh, which has higher production efficiency, simpler process, and can meet the needs of mass production, ensuring the uniformity of distribution (isotropy) of the two-component resin in the mesh, making the "skeleton" structure more reasonable.

[0052] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components;

[0054] Figure 1 It is a schematic diagram of the morphological structure of the dry fiber composite material / preform;

[0055] Figure 2 Schematic diagram of lightweight mesh array electrospinning. DETAILED DESCRIPTION

[0056] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0057] The present invention discloses a lightweight mesh yarn for toughening fiber composite materials, wherein the lightweight mesh yarn is composed of A filaments and B filaments, wherein the A filaments and the B filaments are respectively spun from solution A and solution B;

[0058] The composition of solution A is as follows by mass percentage: 5-30% of low melting point component and 70-95% of solvent. The A filament is a solute filament formed by the low melting point component, and the solvent is completely volatilized during the spinning process.

[0059] The composition of solution B is as follows by mass percentage: 8-35% of high melting point component and 65-92% of solvent. B filaments are solute filaments formed by the high melting point component, and the solvent is completely volatilized during the spinning process.

[0060] The lightweight mesh yarn is composed of A filaments and B filaments. A filaments and B filaments are spun from solution A and solution B respectively. The spinning method is electrostatic spinning, so the spinning solution is stretched by the electrostatic field and the solvent is volatilized, and finally the solute filaments are formed (A filaments and B filaments are corresponding solutes, and the solvent has evaporated completely), that is, the components of the lightweight mesh yarn are a low melting point component (A filament) and a high melting point component (B filament).

[0061] Specifically, the melting point range of A wire is 100-160℃. The role of this component in laying is to ensure the fit between the mesh and the carbon fiber tape. A wire is a crystalline thermoplastic resin with a low melting point. The solute and solvent content are mainly controlled according to the spinnability and spinning effect. Too low content will cause the A wire to fail to form continuous fibers (droplets exist), affecting the subsequent infusion effect and mechanical properties of the composite material. Too high content will cause the solution viscosity to be too high, and the electrostatic force will not be able to stretch the solution into filaments. This component plays a role in bonding and toughening. During the laying process, the A wire is melted by setting a suitable temperature (reaching the melting point of the solute) to bond the mesh to the carbon fiber tape; fiber bridging is the main toughening mechanism.

[0062] Specifically, the B filaments are composed of amorphous thermoplastic resins and have a high melting point, ranging from 300°C to above. The role they play in laying is to maintain the skeleton structure of the mesh, thereby supporting the interlayer and promoting the flow and penetration of the resin, and improving the processability of liquid molding. The solute and solvent content in solution B is mainly controlled according to the spinnability and spinning effect. If the solute content is too low, the B filaments will not be able to form continuous fibers (droplets will exist), affecting the subsequent infusion effect and mechanical properties of the composite material. If the solute content is too high, the solution viscosity will be too high, and the electrostatic force will not be able to stretch the solution into filaments.

[0063] In general, the B wire plays a supporting and toughening role, maintaining the skeleton structure of the lightweight mesh during the resin infusion process, thereby promoting the flow of resin, accelerating the resin infusion speed, and reducing the time it takes for the composite material to be penetrated; ex-situ toughening is the main toughening mechanism.

[0064] Specifically, both A and B fibers contribute to the toughening of the dry fiber composite material. Combined with the specific process, A and B fibers enhance the toughness of the dry fiber composite material through the synergistic effect of fiber bridging and ex-situ toughening.

[0065] Specifically, the low melting point component is one or more of polyamide (PA), polyacrylonitrile (PAN), polyurethane (PU), and polyester (PET). These substances have low melting points and are thermoplastic substances, and are not compatible with epoxy resins. During the laying process, by setting a suitable temperature (corresponding to their melting points), they can be melted (semi-melted) and have adhesion, so that the mesh yarn can be effectively bonded to the carbon fiber tape, improving the processability of the composite process; on the other hand, thermoplastic polymers can improve the interlaminar toughness of the composite material to a certain extent.

[0066] Specifically, the high melting point component is one or more of polyethersulfone (PES), polyetherimide (PEI), polyetheretherketone (PEEK), and polyetherketone (PEK). These substances have high melting points and are thermoplastic substances, and have a certain similar miscibility with epoxy resin. During the resin infusion process, these substances have high melting points and can maintain the skeleton structure and promote resin flow. During the curing process, they can play a role of ex-situ toughening due to similar miscibility.

[0067] Specifically, the first solvent or the second solvent is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), anhydrous formic acid, acetic acid, and ethyl acetate, and the first solvent and the second solvent may be the same or different. The above solvents can effectively dissolve the above high and low melting point components, thereby preparing a uniform and stable spinning solution for spinning; in order to ensure the uniformity of the lightweight mesh yarn, the first solvent and the second solvent are preferably the same solvent.

[0068] Preferably, the A and B fibers in the lightweight mesh are evenly distributed alternately. In fact, due to the particularity of electrospinning, the mesh made therefrom is a non-woven material, that is, a material similar to meltblown cloth, belonging to the non-woven fabric category, and therefore cannot be described by warp and weft weaving or layered distribution in traditional textiles. However, compared to meltblowing technology, electrospinning technology can obtain a finer fiber structure (nanoscale) by controlling process parameters. Figure 2 As shown, solution A and solution B are injected into adjacent electrospinning needles respectively, and the arrangement of the solutions in the needles is "ABAB..." until n, where n is a positive integer not less than 2, preferably an even number; wherein n can be determined according to the required lightweight mesh size. In other words, "one needle spins solution A, and one needle spins solution B" in a cycle.

[0069] It is worth mentioning that "alternating uniform distribution" can be simply understood as follows: if there are two solutions A and B in each needle, that is, mixed silk containing components A and B can be released from each needle, then the mesh formed as a whole is actually the most uniform (because components A and B are present in each fiber); but in actual implementation, electrospinning cannot achieve two-component solutions with one needle, so adjacent needles are selected to "spin solution A with one needle and solution B with another" to achieve the above effect. In other words, it is not that the A and B silks are evenly distributed alternately, but that the needles for preparing the A silk and the needles for preparing the B silk are evenly distributed alternately, and the entire needle array can spin a mesh, and the mesh as a whole evenly contains the A and B silks.

[0070] The lightweight mesh yarn is isotropic. The best way is to evenly distribute A and B wires alternately, because this ensures that A wires play a shaping role in all directions, and B wires play a guiding role, that is, isotropic, and the lack of directionality can make the prepared composite material have the best performance. In fact, A and B wires can also adopt other distribution forms, but it will affect the comprehensive performance of the composite material prepared therefrom; however, in some special cases, when an anisotropic composite material is required, the distribution form of A and B wires can be adjusted to achieve anisotropy, but in view of the fact that electrospinning technology is still being continuously improved and advanced, it is still relatively difficult to obtain anisotropic composite materials through this textile method, or in other words, although anisotropy can be achieved, the performance in each direction is not completely controllable.

[0071] Furthermore, the surface density of the lightweight mesh is 4 to 20 g / m 2 , thickness is 15~80μm.

[0072] The surface density and thickness are mainly controlled by the solution mass concentration, liquid supply, voltage, collection distance and winding speed; the above parameters interact with each other, and are generally preliminarily determined and finally selected through a combination of theoretical experience and experimental adjustment. The parameter combination required to obtain the above-mentioned surface density and thickness lightweight mesh is detailed below.

[0073] Limiting the above parameters can ensure that the proportion of mesh in the composite material, that is, the fiber volume fraction is appropriate, which can effectively ensure the excellent mechanical properties of the composite material. If the above parameters are too low or too high, the fiber volume fraction will be affected, resulting in unstable mechanical properties of the composite material.

[0074] The present invention also discloses a method for preparing the lightweight mesh, comprising the following specific steps:

[0075] S1: Weigh or measure the low melting point component of A silk and the solvent according to the preset formula and mix them, and stir them under heating until they are evenly mixed to obtain solution A;

[0076] S2: Weigh or measure the high melting point component of B silk and the solvent according to the preset formula and mix them, and stir them under heating until they are evenly mixed to obtain solution B;

[0077] S3: Injecting solution A and solution B into alternating needles of the array electrospinning device, that is, injecting solution A and solution B into any adjacent needles, respectively, and setting process parameters and winding speed;

[0078] S4: Perform electrospinning to obtain a finished lightweight mesh yarn.

[0079] Specifically, the heating temperature in step S1 is 25-60°C, such as 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, and the stirring time is 4-10h, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h; the heating temperature in step S2 is 50-95°C, such as 50°C, 65°C, 75°C, 88°C, 93°C, and the stirring time is 6-12h, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. According to the specific multiple groups of experiments, it was found that the temperature and stirring time within this range are sufficient to prepare a uniform and stable spinning solution.

[0080] Specifically, the process parameters in step S3 are: liquid supply: 0.5-6 ml / h, +20-35 kV voltage at the needle tip, -5-0 kV voltage at the receiving area, spinning spacing 10-30 cm, ambient temperature 30-42 ° C, ambient relative humidity 33-48%, and winding speed 0.1-17 m / min.

[0081] The above process parameters are obtained based on theoretical experience summary and adjustment based on a large amount of experimental data, and can achieve the preparation of lightweight mesh with good fiber morphology, thickness and surface density meeting the standards.

[0082] The invention also discloses a dry fiber composite material, which is made from the above-mentioned light mesh yarn.

[0083] The present invention also discloses a dry fiber composite material, which is made from the above-mentioned lightweight mesh yarn. The above-mentioned dry fiber composite material has a type I interlaminar fracture toughness of up to 0.82 KJ / m 2 , Type II interlaminar fracture toughness can reach 2.43KJ / m 2 , the compression strength after impact can reach 244.5MPa.

[0084] Exemplarily, the dry fiber composite material can be prepared by the following method:

[0085] Laying: unwind the carbon fiber mother tape, lay the above-mentioned lightweight mesh yarn on the upper layer of the carbon fiber tape and laminate it, then sprinkle the setting agent, and set the hot pressing process at the same time;

[0086] Specifically, the upper and lower hot rollers are hot pressed at a temperature of 100-160°C (corresponding to the low melting point components, which are melted to ensure the bonding effect between the mesh and the carbon tape), and then the dry fiber preform is obtained through pre-slitting, winding and other processes.

[0087] Liquid molding: The dry fiber preform is layered and infused with epoxy resin under vacuum pressure, and a dry fiber composite material is obtained after curing.

[0088] The type of epoxy resin required for infusion can generally be summarized as bisphenol A epoxy resin; the parameter of infusion amount is difficult to quantify specifically, because the resin of the composite material prepared by the VARI process will overflow the composite material board (more is better than less), and the amount of resin required varies depending on the size of the board. Generally speaking, the required resin infusion amount for common standard specifications of test composite materials is 300 to 400 grams.

[0089] Example 1

[0090] a) Weigh a certain amount of polyamide, anhydrous formic acid and acetic acid to prepare a solution A with a mass concentration of 22wt.%, wherein the mass ratio of anhydrous formic acid to acetic acid is 5:5, and stir at room temperature for 8h; weigh a certain amount of polyethersulfone and dimethyl sulfoxide to prepare a solution B with a mass concentration of 26wt.%, and stir at 70°C for 10h.

[0091] b) Solution A and solution B were placed in the syringe of the array electrospinning device respectively, and were placed alternately in ABAB..., and electrospinning was performed under the conditions of liquid supply 2ml / h, +28kV voltage at the needle, -2kV voltage at the receiving area, spinning spacing 18cm, ambient temperature 35℃, and ambient relative humidity 38%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed was 5m / min, reaching a surface density of 8g / m 2 , thickness is 41μm.

[0092] c) The warped carbon fiber mother tape is unwound, and the prepared electrospinning mesh yarn is laid on the upper layer, and then a setting agent (epoxy resin setting agent) is sprinkled, and the preform is hot-pressed by upper and lower hot rollers at a temperature of 130°C, and then pre-slitting, winding and other processes are performed to obtain a dry fiber preform.

[0093] d) The obtained dry fiber preform is infused with bisphenol A epoxy resin under vacuum pressure and the infusion completion time (composite material is broken down) is recorded, and the infusion amount of bisphenol A epoxy resin is 300-400g.

[0094] e) After the dry fiber preform is cured and formed, it is used for mechanical property testing. The type I interlaminar fracture toughness refers to the standard ASTMD5528 (test loading rate is 1 mm / min); the type II interlaminar fracture toughness refers to the standard ASTM D7905 (test loading rate is 1 mm / min); the post-impact compressive strength refers to the standards ASTM D7136 and ASTM D7137 (test loading rate is 1.25 mm / min).

[0095] Example 2

[0096] a) Weigh a certain amount of polyurethane, DMF and ethyl acetate to prepare a solution A with a mass concentration of 14 wt.%, wherein the mass ratio of DMF to ethyl acetate is 5:5, and stir at 60°C for 10 h; weigh a certain amount of polyetheretherketone and hexafluoroisopropanol to prepare a solution B with a mass concentration of 8 wt.%, and stir at 25°C for 20 h.

[0097] b) Solution A and solution B were placed in the syringe of the array electrospinning device respectively, and were placed alternately using ABAB..., and electrospinning was performed under the conditions of a liquid supply of 5 ml / h, a voltage of +34 kV at the needle, a voltage of -0.5 kV at the receiving area, a spinning spacing of 9 cm, an ambient temperature of 27°C, and an ambient relative humidity of 46%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed of 2 m / min achieved a surface density of 16 g / m 2 , thickness is 72μm.

[0098] c) Similarly, a dry fiber preform is obtained by adopting the same process parameters as in Example 1; based on the same process parameters as in Example 1, resin infusion of the dry fiber preform is completed under vacuum pressure and the infusion completion time is recorded; similarly, the same sample preparation method and test standards as in Example 1 are adopted to obtain the mechanical properties of the dry fiber composite material.

[0099] Example 3

[0100] a) Weigh a certain amount of polyacrylonitrile and DMF to prepare a solution A with a mass concentration of 22 wt.%, and stir at 40°C for 5 h; weigh a certain amount of polyetheretherketone and hexafluoroisopropanol to prepare a solution B with a mass concentration of 8 wt.%, and stir at 25°C for 20 h.

[0101] b) Solution A and solution B were placed in the syringe of the array electrospinning device respectively, and were placed alternately using ABAB..., and electrospinning was performed under the conditions of liquid supply 1ml / h, +17kV voltage at the needle, -3.2kV ​​voltage at the receiving area, spinning spacing 24cm, ambient temperature 40℃, and ambient relative humidity 29%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed was 0.5m / min, reaching a surface density of 14g / m2 , thickness is 67μm.

[0102] c) Similarly, a dry fiber preform is obtained by adopting the same process parameters as in Example 1; based on the same process parameters as in Example 1, resin infusion of the dry fiber preform is completed under vacuum pressure and the infusion completion time is recorded; similarly, the same sample preparation method and test standards as in Example 1 are adopted to obtain the mechanical properties of the dry fiber composite material.

[0103] Example 4

[0104] Weigh a certain amount of polyurethane, tetrahydrofuran (THF) and N,N-dimethylacetamide to prepare solution A with a solution mass concentration of 27wt.%, and stir at 70°C for 20h; weigh a certain amount of polyetherimide, DMF and tetrahydrofuran, wherein the mass ratio of DMF to tetrahydrofuran is 9:1, prepare solution B with a solution mass concentration of 12wt.%, and stir at 30°C for 8h.

[0105] b) Solution A and solution B were placed in the syringe of the array electrospinning device respectively, and were placed alternately using ABAB..., and electrospinning was performed under the conditions of a liquid supply of 4 ml / h, a voltage of +13 kV at the needle, a voltage of -2 kV at the receiving area, a spinning spacing of 18 cm, an ambient temperature of 43°C, and an ambient relative humidity of 30%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed was 6 m / min, reaching a surface density of 10 g / m 2 , thickness is 55μm.

[0106] c) Similarly, a dry fiber preform is obtained by adopting the same process parameters as in Example 1; based on the same process parameters as in Example 1, resin infusion of the dry fiber preform is completed under vacuum pressure and the infusion completion time is recorded; similarly, the same sample preparation method and test standards as in Example 1 are adopted to obtain the mechanical properties of the dry fiber composite material.

[0107] Example 5

[0108] a) Weigh a certain amount of polyurethane and DMAc to prepare a solution A with a mass concentration of 18 wt.%, and stir at 65°C for 9 h; weigh a certain amount of polyethersulfone and DMF to prepare a solution B with a mass concentration of 20 wt.%, and stir at 80°C for 10 h.

[0109] b) Solution A and solution B were placed in the syringe of the array electrospinning device respectively, and were placed alternately using ABAB..., and electrospinning was performed under the conditions of liquid supply of 6 ml / h, +19 kV voltage at the needle, -2.2 kV voltage at the receiving area, spinning spacing of 13 cm, ambient temperature of 37 ° C, and ambient relative humidity of 34%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed was 3 m / min, reaching a surface density of 13 g / m 2 , thickness is 63μm.

[0110] c) Similarly, a dry fiber preform is obtained by adopting the same process parameters as in Example 1; based on the same process parameters as in Example 1, resin infusion of the dry fiber preform is completed under vacuum pressure and the infusion completion time is recorded; similarly, the same sample preparation method and test standards as in Example 1 are adopted to obtain the mechanical properties of the dry fiber composite material.

[0111] Comparative Example 1

[0112] In this comparative example, the preparation process of the electrospinning mesh yarn was omitted, that is, the mesh yarn was not laid to prepare the dry fiber preform and complete the liquid molding process to obtain the dry fiber composite material. Based on the same process parameters as in Example 1, the resin infusion of the dry fiber preform was completed under vacuum pressure and the infusion completion time was recorded; similarly, the same sample preparation method and test standards as in Example 1 were used to obtain the mechanical properties of the dry fiber composite material.

[0113] Comparative Example 2

[0114] a) In this comparative example, only low-melting-point thermoplastic resin was used to prepare electrospinning mesh yarn, and a certain amount of polyamide, anhydrous formic acid and acetic acid were weighed to prepare a solution A with a solution mass concentration of 22 wt%, wherein the mass ratio of anhydrous formic acid to acetic acid was 5:5 (accounting for the mass of the total solvent), and the solution was stirred at room temperature for 8 h;

[0115] b) Solution A was placed in a syringe of an array electrospinning device, and electrospinning was performed under the conditions of a liquid supply of 2 ml / h, a voltage of +28 kV at the needle, a voltage of -2 kV at the receiving area, a spinning spacing of 18 cm, an ambient temperature of 35°C, and an ambient relative humidity of 38%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed was 5 m / min to achieve a surface density of 8 g / m 2 , thickness is 41um.

[0116] c) Similarly, a dry fiber preform is obtained by adopting the same process parameters as in Example 1; based on the same process parameters as in Example 1, resin infusion of the dry fiber preform is completed under vacuum pressure and the infusion completion time is recorded; similarly, the same sample preparation method and test standards as in Example 1 are adopted to obtain the mechanical properties of the dry fiber composite material.

[0117] Comparative Example 3

[0118] a) In this comparative example, only a high melting point thermoplastic resin is used to prepare an electrospinning mesh yarn. A certain amount of polyetheretherketone and hexafluoroisopropanol are weighed to prepare a solution B with a mass concentration of 8 wt%, and the solution is stirred at 30° C. for 24 h;

[0119] b) Solution B was placed in a syringe of an array electrospinning device, and electrospinning was performed under the conditions of a liquid supply of 2 ml / h, a voltage of +28 kV at the needle tip, a voltage of -2 kV at the receiving area, spinning, a spacing of 18 cm, an ambient temperature of 35°C, and an ambient relative humidity of 38%. The surface density of the mesh was regulated by controlling the winding speed, and the winding speed was 5 m / min to achieve a surface density of 8 g / m 2 , thickness is 41um.

[0120] c) Similarly, a dry fiber preform is obtained by adopting the same process parameters as in Example 1; based on the same process parameters as in Example 1, resin infusion of the dry fiber preform is completed under vacuum pressure and the infusion completion time is recorded; similarly, the same sample preparation method and test standards as in Example 1 are adopted to obtain the mechanical properties of the dry fiber composite material.

[0121] Test Results

[0122] Performance test results summary table

[0123]

[0125]

[0126] The main difference between the embodiment and the comparative example is the presence or absence of mesh, and the single melting point component or double melting point component of the mesh. First, the comparative example 1 without mesh is not as good as other experimental examples in terms of infusion time and mechanical properties, because the presence of mesh can effectively improve the mechanical properties of the composite material and play a role in resin diversion. Compared with other embodiments, comparative examples 2 and 3 are the difference between single melting point and double melting point. Since comparative example 2 does not have a high melting point, the infusion process takes a long time and the overall mechanical properties are low; since comparative example 3 does not have a low melting point, although the infusion time is short, some mechanical properties are low. Examples 1 to 5 are all toughened with double-component melting point mesh, the infusion time is relatively short, and the overall mechanical properties are good.

[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A lightweight mesh for toughening fiber composite materials, characterized in that: The lightweight mesh comprises: The components of the light mesh yarn are a low melting point component and a high melting point component; The melting point range of the low melting point component is 100-160° C., and the low melting point component is incompatible with the epoxy resin; The high melting point component has a melting point range of above 300° C., and the high melting point component is miscible with the epoxy resin; The light mesh yarn is woven by using A wire with a lower melting point and B wire with a higher melting point; The A wires and the B wires both have nano-scale fiber structures, the A wires and the B wires in the light mesh are alternately and evenly distributed, and the light mesh is isotropic; The surface density of the lightweight mesh is 4 to 20 g / m 2 , thickness is 15~80μm.

2. The lightweight mesh for toughening fiber composite materials according to claim 1, characterized in that: The A wire is subjected to a hot pressing process during the laying process to play a role in bonding the carbon fiber tape, thereby ensuring the structural integrity of the dry fiber preform; the B wire still maintains a complete structure after the hot pressing process, thereby ensuring the interlayer distance of the composite material.

3. The lightweight mesh for toughening fiber composite materials according to claim 1, characterized in that: During the resin infusion process, the high melting point component can maintain the skeleton structure and promote resin conduction. During the curing process, due to similar solubility, it plays a role of ex-situ toughening.

4. The lightweight mesh for toughening fiber composite materials according to claim 1, characterized in that: The low melting point component is a crystalline thermoplastic resin, and the high melting point component is an amorphous thermoplastic resin.

5. The lightweight mesh for toughening fiber composite materials according to any one of claims 1 to 4, characterized in that: The low melting point component is one or more of polyamide, polyacrylonitrile, polyurethane, and polyester, and / or the high melting point component is one or more of polyether sulfone, polyether imide, polyether ether ketone, and polyether ketone.

6. A method for preparing a lightweight mesh, characterized in that: Used to prepare the lightweight mesh according to any one of claims 1 to 5, the preparation method of the lightweight mesh comprising: S1: Weigh or measure the low melting point component of A silk and the solvent according to the preset formula and mix them, and stir them under heating until they are evenly mixed to obtain solution A; S2: Weigh or measure the high melting point component of B silk and the solvent according to the preset formula and mix them, and stir them under heating until they are evenly mixed to obtain solution B; S3: Injecting solution A and solution B into alternating needles of the array electrospinning device, that is, injecting solution A and solution B into any adjacent needles, respectively, and setting process parameters and winding speed; S4: Perform electrospinning to obtain a finished lightweight mesh yarn.

7. A method for using a lightweight mesh, characterized in that: The light mesh is the light mesh according to any one of claims 1 to 5 or the light mesh obtained by the preparation method according to claim 6, and the method for using the light mesh includes: Laying: The carbon fiber mother tape is unwound, the lightweight mesh yarn is laid on the upper layer of the carbon fiber tape and laminated, and then a setting agent is sprinkled, and a hot pressing process is set at the same time; Liquid Forming: The dry fiber preform is layered and infused with epoxy resin under vacuum pressure. After curing, a dry fiber composite material is obtained to realize the use of lightweight mesh.

8. A method for preparing a dry fiber composite material, characterized in that: The preparation method of the dry fiber composite material is prepared by using the lightweight mesh yarn according to any one of claims 1 to 5 or the lightweight mesh yarn obtained by the preparation method according to claim 6, and the preparation method of the dry fiber composite material comprises: Laying: The carbon fiber mother tape is unwound, the lightweight mesh yarn is laid on the upper layer of the carbon fiber tape and laminated, and then a setting agent is sprinkled, and a hot pressing process is set at the same time; Liquid Forming: The dry fiber preform is layered, epoxy resin is infused under vacuum pressure, and a dry fiber composite material is obtained after curing. The preparation of the lightweight mesh includes: Weigh or measure the low melting point component of A silk and the first solvent according to the preset formula, mix them, and stir them under heating until they are evenly mixed to obtain solution A; Weigh or measure the high melting point component of B silk and the second solvent according to the preset formula, mix them, and stir them under heating until they are evenly mixed to obtain solution B; Solution A and solution B are injected into alternating needles of the array electrospinning equipment respectively, that is, the liquid injected into any adjacent needles is solution A and solution B respectively, and the process parameters and winding speed are set: liquid supply: 0.5-6 ml / h, +20-35 kV voltage is set at the needle, -5-0 kV voltage is set in the receiving area, spinning spacing is 10-30 cm, ambient temperature is 30-42 ° C, ambient relative humidity is 33-48%, and winding speed is 0.1-17 m / min to prepare A and B filaments alternately and evenly distributed, isotropic lightweight mesh yarn.

9. The method for preparing a dry fiber composite material according to claim 8, characterized in that: The first solvent or the second solvent is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), anhydrous formic acid, acetic acid, and ethyl acetate.

10. A dry fiber composite material, characterized in that: The dry fiber composite material is prepared by the preparation method of claim 8 or 9.

Citation Information

Patent Citations

  • Mixed-fiber nonwoven fabric, laminate, filtering medium for filter, and methods for manufacturing same

    CN111263835A

  • Method for toughening carbon fiber epoxy resin composite material by blending porous superfine fibers

    CN116790092A

  • Dry fiber belt production method and dry fiber belt

    CN117207557A

  • Automatic dry fiber laying material as well as preparation method and application thereof

    CN117621486A

  • Manufacturing method of geogrid

    EP0989216A1

Cited By

  • Liquid forming composite material and dry-state carbon fiber intermediate material thereof

    CN122253493A